(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the management of prevetion and control of obesity from the perspective of primary care professionals in the State of Pará. Methodology: Cross-sectional study and descriptive characteristics, carried out with health professionals from primary care units in the State of Pará. The sample was selected based on the criteria for the existence of the Growing Healthy Program (GHP) and the Family Health Support Center (FHSC), indicated by the state public health department. Data collection occurred through an online self-administered questionnaire with information related to nutritional care. Data were tabulated in Microsoft Excel® software spreadsheets, with application of descriptive analysis. Results: 15 professionals participated in the study, regarding the mapping of the territory and/or Health Map of the territory, it was indicated that 60.0% performed, 73.33% performed data analysis/diagnosis of users and the territory and, in 53.33% of the units, the team internally discusses the indicators of Food and Nutrition Surveillance in the territory. The Food and Nutrition Surveillance (FNS) action most adopted by the units is the measurement of weight and height and BMI calculation (80%). 33.3% reported the presence of the Overweight and Obesity Care Line program. The prevailing strategy in the treatment of overweight and obesity was nutritional care (86.6%). Conclusion: Stands out the lack of knowledge and discussion by professionals about programs and indicators, as well as the absence of mechanisms to assess the satisfaction of care provided in the units.